2020
DOI: 10.1101/2020.09.25.309914
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prophylactic intranasal administration of a TLR2 agonist reduces upper respiratory tract viral shedding in a SARS-CoV-2 challenge ferret model

Abstract: Respiratory viruses such as coronaviruses represent major ongoing global threats, causing epidemics and pandemics with huge economic burden. Rapid spread of virus through populations poses an enormous challenge for outbreak control. Like all respiratory viruses, the most recent novel human coronavirus SARS-CoV-2, initiates infection in the upper respiratory tract (URT). Infected individuals are often asymptomatic, yet highly infectious and readily transmit virus. A therapy that restricts initial replication in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Furthermore, it has not escaped our attention that INNA-X treatment can be implemented as a multi-dosing regimen to extend and provide continuous protection throughout the course of an outbreak. Of note and highly relevant to COVID19, our recent studies have since demonstrated its protective efficacy against SARS-CoV-2 in a ferret model (46) establishing proof-of-concept that this strategy can be applied in the face of rapidly spreading pandemic viruses to protect immunologically naïve global populations.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, it has not escaped our attention that INNA-X treatment can be implemented as a multi-dosing regimen to extend and provide continuous protection throughout the course of an outbreak. Of note and highly relevant to COVID19, our recent studies have since demonstrated its protective efficacy against SARS-CoV-2 in a ferret model (46) establishing proof-of-concept that this strategy can be applied in the face of rapidly spreading pandemic viruses to protect immunologically naïve global populations.…”
Section: Discussionmentioning
confidence: 85%
“…20,22,28 TLR agonists could also be used as prophylactic drugs for SARS-CoV-2. Proud et al 29 revealed that prophylactic administration of TLR2/6 agonist reduces SARS-CoV-2 transmission and provides protection against COVID-19. Stimulation of TLR2 leads to activation of the innate immune response, suppression of excessive inflammation and tissue damage, as well as promotion of the integrity of local epithelial barrier function.…”
Section: Tlrs In Sars-cov-2mentioning
confidence: 99%
“…Several PRRs on DCs, including TLR2 [22,42,29], TLR4 [41,21], and DC-SIGN [3,32], have already been demonstrated to bind SARS-CoV-2 proteins. Here we dramatically found that DC-SIGN might give rise to antibody levels but suppress IgG/Ab ratio, which was opposite to DC maturation and function.…”
Section: Discussionmentioning
confidence: 99%